Tehnološke lastnosti in uporabnost lesa velikega pajesena v primerjavi z lesom velikega jesena - Gorišek, Željko (Les (Ljubljana), 2018)
Chinese sumac (Ailanthus altissima (Mill.) Swingle) is one of the most invasive alien species in Europe, and also in Slovenia. Due to its great renewal power the species is spreading rapidly, especially in abandoned agricultural and forest areas and along the traffic routes. It is botanically different from the European ash (Fraxinus excelsior L.), but it has similar tree habitus as well as similar structural characteristics of the wood. For this reason, we analysed the visual, anatomical and some physical and mechanical properties of both wood species. In all anatomical planes, the typical visual and colorimetric similarity of both studied woods was confirmed. Anatomically both ring porous wood species differ mainly in size and distribution of vessels, axial parenchyma and ray tissue. Wood of both species has a similar density as well, but the Chinese sumac has greater shrinkage. Some of the mechanical properties are comparable, although Chinese sumac wood has a lower modulus of elasticity and hardness and greater shear strength than ash wood. We can recommend that the wood of Chinese sumac can be used for production of pulp and paper, various panels and partly for less loaded constructions, which are not exposed to drastic climatic variability.
Keywords: Ailanthus altissima; anatomija lesa; Chinese sumac; European ash; fizikalne lastnosti; Fraxinus excelsior; les; mechanical propertes; mehanske lastnosti; physical propertes; uporaba; use; veliki jesen; veliki pajesen; wood; wood anatomy